PROPERTY MANAGEMENT AMONG SINGLE MOTHERS: ISSUES AND CHALLENGES DURING COVID-19 PANDEMIC - Hannah Hoze Rizal; Farah Safura Muhammud (Journal of Islamic, Social, Economics and Development, 2022)
The issues and challenges on property management among single mothers are becoming a growing concern. The issues and challenges of property management among single mothers cannot be solved simply by providing more parks and spending more money on development and management. There is an urgent need for innovation, for better understanding of the current and potential role of the single mothers in this world. Thus, the issues and challenges of this study need to have their solution. The objective of this research are firstly, to understand the concept of property management in Islam, secondly, to study the main problem of poverty among single mothers, and the third objective, to identify the solution of challenges that mentioned in the Quran. This research is based on data obtained from a survey questionnaire that have been answered by the manager of KWSP, manager of EFP and lawyer Sharie. The data was analysed to evaluate and study the understanding and knowledge more about property management among single mothers like i-sinar, zakat and many more. The research suggested that property management centres like i-sinar and hibah are extremely useful for single mothers who need food, shelter and capital. The results of the study also suggested the level of understanding of property management knowledge is high and helpful to other people to learn. Thus, the results of this study can answer all the objectives by the respondents that I have given questions about the issues and challenges of property management among single mothers in Selangor.